Pengaruh Implementasi E-Lkpd Berbasis Problem Based Learning (Pbl) Terintegrasi Micro Scale Lab Terhadap Hasil Belajar Dan Sikap Terhadap Kimia - Widiantika, Susi Lestari; Junaidi, Eka; Anwar , Yunita Arian Sani (Chemistry Education Practice, 2025)
This research aims to determine the effect of implementing E-LKPD based on Integrated Problem Based Learning (PBL) Micro Scale Lab on learning outcomes and attitudes towards chemistry in class XI colloid materials at SMAN 6 Mataram. The method used is a quasi-experimental method with a non-equivalent control group design. The sampling technique used is purposive sampling, where the researcher deliberately selects samples for certain reasons. The total population in class XI MIPA is 99 people. The number of samples in this study was 68 students in class XI MIPA 1 consisting of 34 students as the experimental class and class XI MIPA 2 consisting of 34 students as the control class. This research used a quantitative research approach. Data analysis was carried out using the normality test, homogeneity test, and hypothesis test (t-test) at a significance level of 0.05 or 5%. The results of the t-test obtained a value of rcount < rtable, namely 0.012 < 0.05, so it can be concluded that the application of the problem based learning model integrated with micro scale lab has a positive effect on student learning outcomes and attitudes towards chemistry at SMAN 6 Mataram in class XI colloid material.